Avaliação da simulação realística como intervenção educativa para capacitação de enfermeiros em ressuscitação cardiopulmonar - Oliveira, Isabela Cristina de (Universidade Federal de São Carlos, 2018)
Introduction: In the context of health, we seek to train proactive and critical thinking. In order for this to happen, the technicalist teaching, part of the model should be replaced by a curriculum for with an active method. In this sense, the realistic simulation, as an active teaching strategy, provides interaction between the task to be performed and simulators, and can be used in a variety of teaching areas, such as training or training of emergency situations. In the context of simulations for emergency capacities, cardiorespiratory arrest (CRP) is an occurrence that requires quick decisions and technical competence. The team which receives frequent training, and which is closely linked to the provided, presents a great differential in the survival of the patients victims of CRP. Objective: To evaluate the realistic simulation as intervention education for the training of nurses in cardiopulmonary resuscitation and perform a follow-up to evaluate the elapsed time of the training. Method: It is a quasi-experimental study, with an intra-participant design, focus on educational intervention and evaluation of the teaching method through realistic simulation, containing nine steps. Results: Between phases IA and IC; ID After 60 days, there was a significant difference (p <0.05) and, between the times IB and ID, there was a difference (p> 0.05), showing that after receiving training after of Time IA respondents appeared to have withheld the knowledge of Time IB up to Time and considerably reduced its performance after 60 days of training. Conclusion: The theoretical training linked to the simulated practice offers performance of participants when compared to the theory. This result shall be maintained within 60 days of the training, as that the participants' scores did not reach the initial indices.
Evaluation of the realistic simulation as an educational intervention for training nurses in cardiopulmonary resuscitation
Keywords: Simulação; Enfermeiros; Reanimação cardiopulmonar; Simulation; Nurses; Cardiorespiratory arrest; Cardiopulmonary resuscitation; CIENCIAS DA SAUDE::ENFERMAGEM